2021
DOI: 10.1001/jamainternmed.2021.3333
|View full text |Cite
|
Sign up to set email alerts
|

The Epic Sepsis Model Falls Short—The Importance of External Validation

Abstract: all medical publications, than advancing the science and art of medicine and the betterment of public health. Today, and for the future, these goals will be accomplished by championing diversity, equity, and inclusion in all aspects of clinical care, biomedical research, health policy, and society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…However, the argument can be made that further evaluation is needed and that variability in results may be related to variability between hospitals and differential workflow creation. 33 One study, particularly highlighting significant change management effort and delivery of alerts via a mobile application in addition to implementation of an algorithm, did demonstrate 53% decrease in mortality. 13 Another study, conducted at 21 hospitals involving 374 838 patients, demonstrated lower mortality, a lower incidence of ICU admission, and a shorter length of hospital stay using a full rapid response intervention program built around a validated deterioration prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the argument can be made that further evaluation is needed and that variability in results may be related to variability between hospitals and differential workflow creation. 33 One study, particularly highlighting significant change management effort and delivery of alerts via a mobile application in addition to implementation of an algorithm, did demonstrate 53% decrease in mortality. 13 Another study, conducted at 21 hospitals involving 374 838 patients, demonstrated lower mortality, a lower incidence of ICU admission, and a shorter length of hospital stay using a full rapid response intervention program built around a validated deterioration prediction model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings in clinical practice strongly reinforce this learning. [ 13,56 ] Unlike the situation for pharmaceutical drugs, in vitro diagnostics (IVD), and medical devices, many digital medicine technologies, particularly in the mobile applications and even software‐as‐medical device (SaMD) segments (classified in the USA as medical device software (MDSW) under the EU's Medical Device Regulation (MDR)) do not have sufficient clinical evidence for efficacy and safety to make clinicians and healthcare organizations confident in implementing them in clinical practice. Evidence is often only developed for technical validity, with insufficient proof of validated usability and only rarely is clinical and health economic evidence of benefit generated.…”
Section: Lack Of Robust Clinical Evidence Basementioning
confidence: 99%
“…The model was later found to have a lower AUC upon external validation than initially reported. 21 Due to the cutoffs used, it was eventually only found to catch 7% of sepsis patients missed by a physician and missed sepsis in 67% of sepsis patients despite generating alerts on 18% of all hospitalized patients. 21 This further underscores the importance of rigorously testing and scrutinizing a model before deployment, as well as having the input of physicians to make sure that the tool is clinically meaningful.…”
Section: Changing Disease Rates In Populations May Render Amentioning
confidence: 99%